Вплив масових часток цукру, полідекстрози і LMA-пектину на міцність модельних мармеладних драглів - Євлаш, Вікторія Владленівна; Yevlash, Viktoria; Аксьонова. О. Ф.; Аksonova, O.; Мануєнков, Д. О.; Manuienkov, D.; Степаненко, С. В.; Stepanenko, S. (Запоріжжя: ТДАТУ, 2025)
UA: У роботі здійснено аналіз сучасних тенденцій виробництва низькокалорійного мармеладу та підкреслено важливість розроблення мармеладу желейного зі зменшеною цукромісткістю. Розглянуто осо-бливості використання та механізми утворення драглів із використанням традиційного високоетерифіко-ванного (HM) та альтернативних низькоетерифікованих (LM, LMA) пектинів. Визначено перспективність заміни до 60% цукру на полідекстрозу для регулювання загального вмісту сухих речовин і формування тек-стурних властивостей з уведенням до рецептури низькоетерифікованих пектинів замість високоетерифіко-ваного. Експериментально досліджено залежність міцності драглів від концентрації низькоетерифікованого LMA-пектину та вмісту цукру і полідекстрози за концентрації іонів кальцію 5 мг/г пектину в модельних системах. Проведено статистичний аналіз отриманих даних, розраховано коефіцієнти рівняння регресії. /// EN: The present study addresses contemporary trends in the development of low-calorie confectionery and substantiates the significance of designing jelly-type marmalade with reduced sugar content. Particular attention is devoted to the functional properties and gelation mechanisms of traditional high-methoxyl pectins compared with alternative low-methoxyl pectins. Popular approaches to partial sucrose replacement in marmalade confectionery products were analyzed. Based on literature data concerning practical features of sweeteners and bulking agents commonly used in low-sugar marmalade technologies, polydextrose was selected for this study.The potential of partial sucrose substitution with polydextrose – up to 60% – was identified as a promising approach for modulating total soluble solids and tailoring textural attributes when incorporating low-methoxyl pectins in place of high-methoxyl analogues.Experimental investigations were carried out on model systems to determine the relationship between gel strength and the concentrations of low-methoxyl amidated (LMA) pectin, sucrose, and polydextrose at a fixed calcium ion level of 5 mg per g of pectin. Preliminary tests indicated that this calcium concentration ensured homogeneous and sufficiently firm gels, avoiding excessive rigidity or syneresis.The results showed that increasing the LMA pectin content within the range of 1.0-1.25% significantly increased gel strength, while higher sucrose content tended to weaken the structure. The optimal ratio of 1.365 g dry LMA pectin per 100 g gel mixture with 50% sugar replaced by polydextrose provided comparable strength to traditional HM pectin gels. Statistical evaluation of the results was performed, and regression models describing the influence of compositional factors on gel strength were established.The fitted regression provided practical prediction of composition–texture relationships, underpinning the use of polydextrose–LMA pectin systems to design reduced-sugar marmalades without loss of gel strength.
Effect of sugar, polydextrose, and LMA pectin mass fractions on the mechanical strength of model marmalade gels
Keywords: мармелад; пектин; цукор; полідекстроза; драглі; міцність; marmalade; pectin; sugar; polydextrose; gels; gel strength